Assessment of the potential of the agricultural cluster initiative of dry grain bean in the productive chains of the Puno region, Peru - Holguino Lope, Yaneth (2021)
Agricultural clusters have received attention from the academic, government, and business community. The study uses an integrated model of cluster initiative: collective initiative, intra-cluster relationship and competitive profile from Putnam (1994); Capó (2008) and Botero (2017). Objectives: To determine the potential of the dry grain bean cluster initiative of the productive chains of the Puno region, Peru; for the implementation of an agricultural cluster. Method: Quantitative approach, non-experimental design, cross-sectional analytical descriptive level, questionnaire survey technique; It shows 3 associations from Huancané, 7 from Yunguyo and 78 surveyed producers; non-probability sampling. Results: It revealed a favorable potential for a dry grain agricultural cluster initiative, based on a high level of collective initiative (84.62%), relationships for associations of the same chain of +1, +2 and -0.5 scores that indicate not present lack of collaboration and competition, and competitive profile (2.83) of the production chain. Conclusions: The proposed integrated agricultural cluster initiative model is useful to determine the potential of the cluster and constitutes a support for the feasibility of implementing a future agricultural cluster.